2012
DOI: 10.1016/j.clim.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 upregulation in peripheral leukocytes and CNS of multiple sclerosis patients

Abstract: Multiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system (CNS). Here we document for the first time that the cytokine IL-33 is upregulated in both the periphery and the CNS of MS patients. Plasma IL-33 was elevated in MS patients compared to normal subjects and a three-month treatment of MS patients with interferon β-1a resulted in significant decrease of IL-33 levels. Similarly, stimulated cultured lymphocytes and macrophages from MS patients had elevated IL-33 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 94 publications
(130 reference statements)
7
88
1
Order By: Relevance
“…Previous studies have mentioned that IFN-β treatment could significantly suppress IL-33 plasma levels (56). In accordance with them, our assessments revealed that plasma levels of IL-33 in IFN-β-treated patients were significantly lower than in untreated patients (p < 001).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have mentioned that IFN-β treatment could significantly suppress IL-33 plasma levels (56). In accordance with them, our assessments revealed that plasma levels of IL-33 in IFN-β-treated patients were significantly lower than in untreated patients (p < 001).…”
Section: Discussionsupporting
confidence: 90%
“…Brain inflammation may be evident in the earlier stages of the disease and may constitute a more reasonable target for drug development (Kozauer and Katz, 2013). Interestingly, IL-33 was also upregulated in astrocytes and peripheral leukocytes of MS patients (Christophi et al, 2012). Moreover, expression of IL-33 and IL-33 genes was increased in patients with remitting-relapsing MS (Zhang et al, 2014).…”
Section: Functional and Pathologic Features Of Il-33 In Allergic Disementioning
confidence: 99%
“…IL-33 has been implicated in MS (Christophi et al, 2012;Zhang et al, 2014). Luteolin has synergistic effect with IFN-b in inhibiting activation of peripheral blood mononuclear cells from MS patients (Sternberg et al, 2008(Sternberg et al, , 2009.…”
Section: Il-33 In Autoimmune and Inflammatory Disordersmentioning
confidence: 99%
“…We showed that UVB-induced IL-33 was involved in immune suppression because antibodies specific for IL-33 could block the effects of UVB exposure . MS patients have elevated levels of this cytokine within the CNS and periphery (Christophi et al 2012), suggesting IL-33 may play a pathogenic role during this disease. Resting mice also express IL-33 and its receptor (ST2) in the CNS, which is upregulated during EAE.…”
Section: Interleukin-33 (Il-33)mentioning
confidence: 99%